Efficacy and safety of traditional Chinese medicine decoction as an adjuvant treatment for diabetic nephropathy: a systematic review and meta-analysis of randomized controlled trials - Zheng, Shuyu; Xu, Yunxi; Zhang, Ya; Long, Caiyi; Chen, Guo; Jin, Zhao; Jiang, Shui; Chen, Junyu; Qin, Yulian (Frontiers in Pharmacology, 2024)
Objective This study aimed to assess the efficacy and safety of traditional Chinese medicine decoction as an adjunctive treatment for diabetic nephropathy in systematic evaluations. Methods A comprehensive search was conducted in PubMed, WOS, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang databases, covering the period from January 2013 to July 2023. The search was restricted to randomized controlled trials (RCTs) conducted within the past decade that investigated the use of TCM decoction as an adjunctive treatment for diabetic nephropathy. The control group received western medicine treatment, while the intervention group received TCM decoction in addition to the conventional treatment. Endnote and Excel were employed for literature management and data organization, and Revman 5.3 and Stata 16 software were used for the analyses. Results 66 RCTs involving 6,951 participants were included in this study. The clinical efficacy of TCM decoction as an adjunctive treatment for diabetic nephropathy was found to be significantly higher than that of the control group (OR = 3.12, 95% CI [2.70, 3.60], I 2 = 0%, P < 0.00001). The incidence of adverse events did not differ significantly between the intervention group and the control group (OR = 0.94, 95% CI [0.60, 1.48], I 2 = 0%, P = 0.94). According to the secondary outcomes of renal function and blood glucose indicators, the intervention group showed better therapeutic efficacy compared to the control group. The most frequently used TCM categories were tonifying medicine, blood-activating medicine, astringent medicine, diuretic medicine, heat-clearing medicine, and laxative medicine. Among them, the top five frequently used Chinese medicine were Astragalus mongholicus Bunge [Fabaceae;Astragali mongholici radix](58 times), Salvia miltiorrhiza Bunge [Lamiaceae;Radix et rhizoma salviae miltiorrhizae] (42 times), Dioscorea oppositifolia L. [Dioscoreaceae;Dioscoreae rhizoma] (38 times), Poria cocos (Schw.) Wolf [Polyporaceae;Poria] (38 times), and Cornus officinalis Siebold & Zucc. [Cornaceae;Corni fructus] (35 times). Conclusion The combined use of TCM decoction with western medicine in the treatment of diabetic nephropathy can enhance clinical effectiveness and 2 This is a provisional file, not the final typeset article achieve superior therapeutic effects in comparison to western medicine alone, without significant risks. Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=529144], identifier [CRD42022529144].